Physical and Microstructural Properties of Coconut (Cocos nucifera) Particleboards Bound with Castor Oil-based Polyurethane Resin - Bispo, Rodrigo Andraus [UNESP]; Rodrigues, Felipe Reis [UNESP]; Cazella, Pedro Henrique da Silva [UNESP]; Silva, Sérgio Augusto Mello da [UNESP]; Aquino, Vinícius Borges de Moura [UNESP]; Moreto, Jeferson Aparecido; Chahud, Eduardo; Branco, Luiz Antonio Melgaço Nunes; Dos Santos, Herisson Ferreira; Lahr, Francisco Antonio Rocco; Christoforo, André Luis (BioResources, 2024)
Particleboards find extensive application in both civil construction and the furniture industry. Nevertheless, concerns about the interaction of panels with humidity require the exploration of alternative sources to develop a product that meets the requirements for use. This work aims to produce single-layer particleboards with coconut fiber (Cocos nucifera) as substrate, bonded with 10% by mass castor oil-based polyurethane resin (CPUR). Two groups of mixtures were proposed, different from each other in the initial moisture content of the Cocos nucifera particles, ranging from 0 to 2% and from 4% to 6%. For this purpose, density (D), thickness swelling after 24 h (TS), moisture content (MC), and water absorption (WA) were evaluated. The Tukey mean contrast test, at a 5% significance level, was used to verify the influence of the initial moisture content of the particles on the physical properties of the particleboards. The microstructure of the composites was assessed through the utilization of scanning electron microscopy (SEM) technique. The results indicated better compaction of the C. nucifera particles, resulting in fewer voids, contributing to the densification of the panels and, with this, the reduction of water absorption by 15.1%.
Keywords: Castor oil-based polyurethane resin; Cocos nucifera; Microstructural properties; Particleboards; Physical properties